Efecto de cuatro hormonas enraizantes sobre varetas de cacao (Teobroma cacao L.) de la variedad CNN-51 en la zona de Babahoyo, provincia Los Ríos - Ledesma Pazmiño, Johanna Alexandra (2023)
The research was carried out at the Faculty of Agricultural Sciences of the Technical University of Babahoyo, in the nursery stage under controlled conditions. As planting material, cocoa cuttings of the CCN 51 variety were used. The treatments consisted of different types of rooting agents such as lentil water, coconut water, Cinnamon, Active commercial rooting agent and an absolute control without application. A completely randomized design was used, with Tukey's test at 5% probability. All the necessary agricultural tasks will be carried out in the proper management of the trial, such as preparation of the substrate and disinfection, filling and assembly of the covers, collection and preparation of the cocoa stakes, application of the rooting agents and sowing. The conclusions determined that the percentage of rooted cuttings at 40 and 60 days, if they had positive effects with the application of organic rooting hormones in cocoa twigs of the CNN-51 variety; the greatest vigor was presented in the treatments that Coconut water was applied in doses of 1 L/20 cocoa twigs, which affected the other treatments; favorable results were obtained in the variables fresh weight and dry weight of the roots, applying coconut water and lentil water; no significant differences were shown regarding the number of shoots; the length of roots obtained dispersion of the results between the use of coconut water and the control; the fresh and dry weight of the aerial part reported averages that fluctuated between 25.4 and 6.4 g, respectively; the height of the shoots at 40 and 60 days reached better averages using coconut water and the highest net benefit was obtained by applying coconut water in doses of 1 L/20 twigs with $45.25